Epidural Use and Clinical Chorioamnionitis among Women Who Delivered Vaginally - Abramovici, Adi; Szychowski, Jeff M.; Biggio, Joseph R.; Sakawi, Yasser; Andrews, William W.; Tita, Alan T. N. (American Journal of Perinatology, 2014)
Objective Chorioamnionitis, an important cause of maternal and neonatal morbidity, is influenced by epidural use and the occurrence of epidural fever. We evaluated the association between chorioamnionitis, histologic placental findings, and intrapartum factors focusing on epidural use.Materials and Methods We conducted a secondary analysis of a randomized controlled trial of different doses of oxytocin to prevent postpartum hemorrhage among women who delivered vaginally. The primary outcome was clinical diagnosis of chorioamnionitis leading to antibiotic therapy. Intrapartum factors examined included epidural use, parity, labor induction, gestational age, maternal age, ethnicity, body mass index, cervical dilatation at admission, preeclampsia/eclampsia, preterm labor, and duration of labor.Results Of the 1,798 women randomized, we excluded 13 multifetal births leaving 1,785 for analysis: 1,491 had an epidural and 294 did not. Of those with epidural, 8.0% had clinically diagnosed chorioamnionitis compared with only 1.0% without epidural: unadjusted odds ratio (OR) = 8.3 (95% confidence interval [CI]: 2.63–26.40); p < 0.0001. After multivariable logistic regression, epidural use (adjusted OR: 5.80; 95% CI: 1.77–19.11), increasing parity (0.42; 0.32–0.55), and preeclampsia (0.31; 0.14–0.66) were significantly associated with chorioamnionitis.Conclusion Epidural use is statistically associated with an increase in clinical diagnosis of chorioamnionitis. A cause and effect relationship cannot be confirmed from this study. Independently of labor duration and increasing parity, preeclampsia appeared protective.
Keywords: epidural; chorioamnionitis; risk factors